Pengembangan Ekowisata Cuku Nyinyi melalui Edukasi dan Transplantasi Terumbu Karang - Delilla Suhanda; Vidya Octaverina; Marisya Apriyanti; Muhammad Arhan Rajab; Rizki Dimas Permana; Adib Mustofa; Tefur Nur Rohman; Mohammad Ashari Dwiputra; Cinta Sri May Yemima Lumban Raja (Agriculture Faculty, Universitas Lampung, 2026)
The Cuku Nyinyi Mangrove Ecotourism Area in Sidodadi Village, Pesawaran Regency, Lampung has strong potential for marine ecotourism based on mangrove, seagrass, and coral reef ecosystems. However, increasing pressure from human activities and changing environmental conditions have led to the degradation of coral reefs, highlighting the need for rehabilitation efforts involving local communities. This community service program aimed to improve the knowledge and skills of ecotourism managers and local residents in coral reef transplantation using the spider-web method as an effort to support conservation and sustainable marine tourism development. The program was implemented through educational sessions on coral reefs, training in the use of diving equipment (SCUBA), construction of transplantation media, coral fragmentation, attachment of coral fragments to spider-web frames, and placement of the media on the seabed at a depth of approximately 5 meters. Activity data were collected through field observations, documentation, and informal discussions and interviews with participants. The results showed active community participation throughout all stages of the program and increased understanding of the importance of coral reef rehabilitation. The transplantation structures were successfully installed, and initial maintenance was carried out by removing algae to reduce competition with coral fragments. The main challenges included participants’ limited experience in using diving equipment and dynamic water conditions. Overall, this program had a positive impact on improving community capacity, strengthening conservation awareness, and supporting the development of educational tourism attractions in the Cuku Nyinyi Ecotourism Area.